An Application of the Modified Expansion Method to Nonlinear Partial Differential Equation - Bulut, Hasan; Akturk, Tolga; Yel, Gülnur (My University, 2018)
In this article, the travelling wave solutions of the medium equal width equation are obtained usingthe modified expansion method. The solution functions were obtained by selecting the appropriate parameters. Ithas been checked that these functions provide the MEW equation. Density, two and three dimensional graphicsof the obtained solutions and other mathematical operations were found with the Mathematica software program.When the resulting solution functions are examined, it is determined that they include trigonometric, topologicaland singular soliton properties.
Keywords: Matematik